2019
DOI: 10.3389/fimmu.2019.02854
|View full text |Cite
|
Sign up to set email alerts
|

WNT Signaling in Tumors: The Way to Evade Drugs and Immunity

Abstract: WNT/β-catenin signaling is involved in many physiological processes. Its implication in embryonic development, cell migration, and polarization has been shown. Nevertheless, alterations in this signaling have also been related with pathological events such as sustaining and proliferating the cancer stem cell (CSC) subset present in the tumor bulk. Related with this, WNT signaling has been associated with the maintenance, expansion, and epithelial-mesenchymal transition of stem cells, and furthermore with two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(152 citation statements)
references
References 214 publications
4
134
0
3
Order By: Relevance
“…Since HAGLR could promote SCL24A2 expression, and SCL24A2 has been found to negatively regulate the Wnt/β-catenin pathway in NSCLC cells [33]. The Wnt/β-catenin signaling is implicated in multiple physiological processes including cell migration, polarization, as well as in maintenance and proliferation of cancer stem cells in the tumor bulk [34]. These findings suggested that activation of Wnt/β-catenin might be responsible for the growth and metastasis of LC cells.…”
Section: Discussionmentioning
confidence: 95%
“…Since HAGLR could promote SCL24A2 expression, and SCL24A2 has been found to negatively regulate the Wnt/β-catenin pathway in NSCLC cells [33]. The Wnt/β-catenin signaling is implicated in multiple physiological processes including cell migration, polarization, as well as in maintenance and proliferation of cancer stem cells in the tumor bulk [34]. These findings suggested that activation of Wnt/β-catenin might be responsible for the growth and metastasis of LC cells.…”
Section: Discussionmentioning
confidence: 95%
“…[28][29][30][31] Wnt/β-catenin signalling is essential for both tumour progression and the anti-tumour immune system. 9,20 The activation of β-catenin inhibits the transcription of chemokines C-C motif chemokine ligand 4 (CCL4) and reduces the recruitment and activation of basic leucine zipper ATF-like transcription factor 3 (BATF3)-lineage dendritic cells (DC) in the tumour microenvironment, thereby reducing the level of DC-derived C-X-C motif chemokine ligand 10 (CXCL10) and ultimately affecting the recruitment of T cells into the TME. 11,32 The Wnt/β-catenin signal activates T cell factor 1 (TCF-1) and blocks the transcriptional activity of forkhead box P3 (FoxP3) to affect the in ltration of regulatory T cells (Treg) into TME and dampen immunosuppressive activity of Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/β-catenin signalling is associated with mechanistic development of immunity evasion, 20 and we previously showed that CDK5RAP3 negatively regulates the Wnt/β-catenin signalling pathway. We rst explored the responsiveness of patients to chemotherapy after inclusion of TIL.…”
Section: The Expression Of Ckd5rap3 In Combination With Til Can Affecmentioning
confidence: 99%
“…On the other hand, extrinsic resistance occurs external to tumor cells through changes in T-cell activation. This involves regulatory T-cells (Tregs) [ 28 ], myeloid derived suppressor cells (MDSCs) [ 29 ], tumor-associated macrophages (TAMs) [ 30 ] and multiple canonical pathways [ 31 ] affecting the percentage of tumor infiltrating lymphocytes (TILs) and influencing the cytokine profile and cell toxicity [ 32 ].…”
Section: Mechanisms Of Resistance To Immunotherapy and Ways To Ovementioning
confidence: 99%